A Novel Asp121Asn Mutation of Myelin Protein Zero Is Associated with Late-Onset Axonal Charcot-Marie-Tooth Disease, Hearing Loss and Pupil Abnormalities - Duan, Xiaohui; Gu, Weihong; Hao, Ying; Wang, Renbin; Wen, Hong; Sun, Shaojie; Jiao, Jinsong; Fan, Dongsheng (Frontiers in Aging Neuroscience, 2016)
Myelin protein zero (MPZ) is a major component of compact myelin in peripheral nerves. Mutations in MPZ have been associated with different Charcot–Marie–Tooth disease (CMT) phenotypes (CMT1B, CMT2I/J, CMTDI), Dejerine–Sottas syndrome, and congenital hypomyelination neuropathy. Here, we report phenotypic variability in a four-generation Chinese family with the MPZ mutation Asp121Asn. Genetic testing was performed on 9 family members and 200 controls. Clinical, electrophysiological and skeletal muscle MRI assessments were available for review in 6 family members. A novel heterozygous missense mutation, Asp121Asn, was observed in 5 affected members of the family. Unaffected relatives and 200 normal controls were without the mutation. Four of the affected members of the family displayed late-onset, predominantly axonal sensory and motor neuropathy, pupil abnormalities, and progressive sensorineural hearing loss. One young affected member presented with Argyll–Robertson pupils and diminished deep tendon reflexes in the lower limbs. The MPZ mutation Asp121Asn may be associated with late-onset axonal neuropathy, early-onset hearing loss and pupil abnormalities. Our report expands the number and phenotypic spectrum of MPZ mutations.